The relationship between sense of coherence and emotional intelligence as individual health assets for mental health promotion in students and healthcare professionals: a scoping review - Urtubia-Herrera, Valentina; Navarta-Sánchez, María Victoria; Palmar-Santos, Ana María; Pedraz-Marcos, Azucena; García-Gomez, Alberto; Luis, Elkin O.; Bermejo-Martins, Elena (Frontiers in Public Health, 2024)
Introduction: Workplace Mental health promotion in healthcare sector, is a global priority due to the stress associated with caregiving environments and the increase of mental health problems among health professionals and students. The role of emotional intelligence (EI) and sense of coherence (SOC) have been identified as critical health protectors. However, the relationship between them as well as the underlying mechanisms of these relationships on health benefits in this population is still unclear. Aim: To synthetize the existing literature on the relationship between emotional intelligence and sense of coherence, as well as their mutual impact on healthcare workers' and student's well-being. Method: A scoping review was conducted following the Joanna Briggs Institute guidelines. A systematic search was conducted in PsyCINFO, CINHAL, SCOPUS and PUBMED databases, using key-terms such as students, health professionals, emotional intelligence, and sense of coherence. Results: A total of 11 articles were included, with a range of years from 2014 to 2022. Evidence was found to support the positive relationship between sense of coherence and emotional intelligence. The use of EI as a training pathway to improve SOC and health promoting behaviors is suggested. The benefits of intervening on these factors contribute to improved health professionals' and students' general well-being and motivation for a better performance, either in their studies or clinical work. Conclusion: The positive relationship between emotional intelligence and a sense of coherence has direct and indirect benefits on students' and healthcare professionals' well-being. Future studies should address longitudinal and experimental analysis to confirm these findings.